Exploration of Non-Covalent Interactions of Lithium Salts in Acetonitrile-Water Binaries with the Manifestation of Solvation Consequences - Samir Das; Koyeli Das; Niloy Roy; Deepak Ekka; Mahendra Nath Roy (International Journal of Research in Chemistry and Environment (IJRCE), 2018)
The properties of material like densities and viscosities of some selected lithium salts (namely, lithium nitrate, lithium iodide and lithium acetate) have been studied in acetonitrile-water binary mixed solvent systems at the temperature 298.15K. Apparent molar volumes (fV) and viscosity B coefficients of these salts are obtained from these data supplemented with their densities and viscosities, respectively. Limiting apparent molar volumes (fV°) and experimental slopes (SV*) derived from density date using Masson equation have been interpreted in terms of ion-solvent and ion-ion interactions, respectively. The viscosity data have been analyzed using Jones-Dole equation, and derived parameters B and A have also been interpreted in terms of ion-solvent, ion-ion interactions, respectively. It has been observed from the both derived parameters the ion-solvent interaction is predominant than interaction of ions (ion-ion) itself in all the studied binaries. Furthermore, the structure making/breaking capacities of salts investigated have been discussed in terms of the rearrangement with symmetrically of the interacting ions. Another two parameters, refractive index and conductivity have been taken into account to give explanation and confirming the same results occurring into the studied solutions system.